Studi Eksperimental dan Analisis Optimasi Adsorpsi Cu(II) Menggunakan Kulit Pinang dengan Variasi Massa, pH, dan Suhu - Sabollah, Siti Halijah; Tuheteru, Hajirum; Rahman, Ainul Alim; Fadlil, Firmanullah (Universitas Nurul Jadid, 2025)
The rapid growth of fisheries in Sorong city has led to severe marine pollution, especially elevated Cu II concentrations that exceed water‑quality standards and threaten both ecosystems and human health. This study aimed to develop an eco‑friendly adsorbent from agricultural waste, namely citric‑acid‑activated palm‑shell powder, for the removal of Cu II from fishing‑industry effluents. The palm‑shell powder was activated by immersion in 0.1 M citric acid for 24 h, which introduced carboxyl groups, eliminated impurities, and increased porosity and surface functionality, thereby enhancing Cu II sorption capacity. A full‑factorial experimental design was employed, testing three independent variables (adsorbent mass, solution pH, and temperature) each in triplicate, with a fixed contact time of 120 min, sample volume of 50 mL, and initial adsorbent pH 6. Optimal conditions were identified as 50 mg adsorbent (capacity = 8.354 mg L⁻¹, removal efficiency = 54.14 %), pH 9 (capacity = 10.69 mg L⁻¹, efficiency = 69.28 %), and 60 °C (capacity = 7.49 mg L⁻¹, efficiency = 48.56 %). The citric‑acid‑activated palm‑shell adsorbent demonstrated significant Cu II reduction in fishing‑effluent water and presents a low‑cost, locally available, and sustainable solution for the treatment of fisheries waste streams.